The semantic aspect of comparing English and Ukrainian phraseological units (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The paper examines the semantic aspect of comparing English and Ukrainian set expressions, the problem of interlingual relations at the lexical level. It studies the cases of equivalence, inclusion, overlapping and non-equivalence in the systems of English and Ukrainian phraseology.
Keywords: interlingual relations; phraseological system; equivalence; inclusion; overlapping; non-equivalence